2022
DOI: 10.3389/fpsyg.2022.943779
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship education of college students and entrepreneurial psychology of new entrepreneurs under causal attribution theory

Abstract: With the rapid development of information technology, the society’s demand for innovative talents has become increasingly prominent. The purpose of this study is to optimize the teaching strategies of entrepreneurship education for college students, further cultivate college students’ entrepreneurial ideas, and promote the formation of entrepreneurial values. The problems existing in entrepreneurship education in colleges and universities are studied based on entrepreneurial psychology and attribution theory. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…On the other hand, having the necessary skills of EOI to initiate entrepreneurial activities alone is not necessarily leading to university students' entrepreneurial behaviors; educators need to equip students with positive psychological resources, such as PC, which can be developed and taught. Various measures could be adopted by educators to improve students' levels of PC, such as local case studies and face-to-face discussions with successful entrepreneurs (Su et al, 2020 ; Xie et al, 2022 ). The training and learning process of PC could positively affect students' EI by increasing their level of creativity, information processing ability, and intellectual fluency, which, in turn, enhances the chances to act upon identified business opportunities (Ephrem et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, having the necessary skills of EOI to initiate entrepreneurial activities alone is not necessarily leading to university students' entrepreneurial behaviors; educators need to equip students with positive psychological resources, such as PC, which can be developed and taught. Various measures could be adopted by educators to improve students' levels of PC, such as local case studies and face-to-face discussions with successful entrepreneurs (Su et al, 2020 ; Xie et al, 2022 ). The training and learning process of PC could positively affect students' EI by increasing their level of creativity, information processing ability, and intellectual fluency, which, in turn, enhances the chances to act upon identified business opportunities (Ephrem et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Originally, as a psychological construct in the field of organizational management, previous studies have concentrated mainly on the positive relationship between PC and employees' engagement, employees' innovative intention, job satisfaction, business excellence, and organizational performance (Luthans et al, 2007b ; Nolzen, 2018 ; Alshebami, 2021 ; Saleem et al, 2022 ; Zhang et al, 2022 ). Entrepreneurs' mental states and entrepreneurial ideas play a key role in their entrepreneurial decisions; hence, the effects of PC on entrepreneurial activity may also exist in the field of business (e.g., Baluku et al, 2016 ; Su et al, 2020 ; Xie et al, 2022 ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Entrepreneurial education in higher education is an area with a very rapid growth and the core of innovation and entrepreneurship education is to cultivate university students' innovative spirit and entrepreneurial ability (Xie, Luo, Zheng, & Ma, 2022). This phenomenon started at the University of Southern California in the early 1970's and, in 2005, there were more than 2200 courses at over 1600 schools (Kuratko, 2005).…”
Section: Entrepreneurial Educationmentioning
confidence: 99%
“…Some studies show that entrepreneurial education has a positive impact and reinforces entrepreneurial intentions (Xie et al, 2022), however, entrepreneurial intentions do not translate into effective firm creation and people who intend to become entrepreneurs will not automatically start-up new firms (Boubker et al, 2022) and one of the most relevant conclusions is the link between the subjects' perception on training and the barriers to entrepreneurship, which is a very new approach since the literature fails to, strongly, explore this link. Also noteworthy is the fact that there was no reference to the legal system, namely the Labour Code, something that Klapper et al, (2006) pointed out as being a barrier.…”
Section: Cluster 2 -Barriersmentioning
confidence: 99%
“…They suggest that the core of innovation and entrepreneurship education is to cultivate college students’ self-efficacy in entrepreneurial decision-making, which plays a mediating role between entrepreneurial education and students’ entrepreneurial intention and identity. The authors concluded with a recommendation that colleges continue to improve the quality of entrepreneurship education and strengthen the cultivation of students’ entrepreneurial spirit and ability (Xie, 2022).…”
Section: Introductionmentioning
confidence: 99%